Pretreatment Blood Brain Barrier Damage and Post Treatment Intracranial Hemorrhage in Patients Receiving IV tPA - Leigh, Richard (2014)
BACKGROUND AND PURPOSE: Early blood brain barrier (BBB) damage after acute ischemic stroke (AIS) has previously been qualitatively linked to subsequent intracranial hemorrhage (ICH). In this quantitative study, it was investigated whether the amount of BBB damage evident on pre-tPA MRI scans was related to the degree of post-tPA ICH in patients with AIS. METHODS: Analysis was performed on a database of patients with AIS provided by the STIR and VISTA Imaging Investigators. Patients with perfusion-weighted imaging (PWI) lesions >10mL and negative gradient-recalled echo (GRE) imaging prior to IV tPA were included. Post processing of the PWI source images was performed to estimate changes in BBB permeability within the perfusion deficit relative to the unaffected hemisphere. Follow-up GRE images were reviewed for evidence of ICH and divided into three groups according to ECASS criteria: no hemorrhage (NH), hemorrhagic infarction (HI), and parenchymal hematoma (PH). RESULTS: 75 patients from the database met the inclusion criteria, 28 of whom experienced ICH, of which 19 were classified as HI, and nine were classified as PH. The mean permeability (±standard deviations), expressed as an index of contrast leakage, was 17.0%±8.8 in the NH group, 19.4%±4.0 in the HI group, and 24.6%±4.5 in the PH group. Permeability was significantly correlated with ICH grade in univariate (p=0.007) and multivariate (p=0.008) linear regression modeling. CONCLUSIONS: A PWI-derived index of BBB damage measured prior to IV tPA is associated with the severity of ICH after treatment in patients with AIS.